Find the minimum possible value of
2 cos 4 θ + 8 cos 3 θ + 3 2 cos 2 θ + 5 6 cos θ + 1 0 0
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f ( θ ) = 2 cos 4 θ + 8 cos 3 θ + 3 2 cos 2 θ + 5 6 cos θ + 1 0 0 . We want to find the minimum value of this function.
Using the trig identities cos 4 θ = 8 cos 4 θ − 8 cos 2 θ + 1 , cos 3 θ = 4 cos 3 θ − 3 cos θ , and cos 2 θ = 2 cos 2 θ − 1 , we substitute and get
f ( θ ) = 1 6 cos 4 θ + 3 2 cos 3 θ + 4 8 cos 2 θ + 3 2 cos θ + 7 0 .
Since this function is differentiable everywhere, to find its minimum value we can examine where its derivative is zero. So we differentiate:
f ′ ( θ ) = − 6 4 cos 3 θ sin θ − 9 6 cos 2 θ sin θ − 9 6 cos θ sin θ + 3 2
And factor:
f ′ ( θ ) = − 3 2 sin θ ( 2 cos θ + 1 ) ( cos 2 θ + cos θ + 1 )
There are no real values of cos θ for which cos 2 θ + cos θ + 1 = 0 . Therefore f ′ ( θ ) = 0 only if either sin θ = 0 or cos θ = − 2 1 . In other words, only if cos θ = − 1 , − 2 1 , or 1 . The respective values of f ( θ ) are 7 0 , 6 3 , and 1 9 8 . Therefore the minimum value of f ( θ ) is 63.
Correction in f' : the last term should be -32 sin theta, not +32.
The first part of the solution is to expand all the cosines into powers of cos ( x ) . This is a very boring part of the solution so i will omit it. In the end, we can replace cos ( x ) = t to get:
7 0 + 3 2 t + 4 8 t 2 + 3 2 t 3 + 1 6 t 4
We will now try to minimize this polynomial, respecting − 1 ≤ t ≤ 1 :
If there is an extreme value the derivative of this function will have to be equal to 0 in that point. The derivative is:
3 2 + 9 6 t + 9 6 t 2 + 6 4 t 3
We have to solve 3 2 + 9 6 t + 9 6 t 2 + 6 4 t 3 = 0
We factor out 32 to get
1 + 3 t + 3 t 2 + 2 t 3 = 0
We will write this in a slightly different way to get
1 + 3 t + 3 t 2 + t 3 = − t 3
That is,
( t + 1 ) 3 = ( − t ) 3
Since the function x 3 is a monotonic function, this implies
t + 1 = − t
Solving this we get t = − 2 1
Replacing this into the starting polynomial we get 63. Note that it is a good idea to also check the endpoints of the interval [ − 1 , 1 ] to make sure that the minimum is not there.
It is well known that, for any positive integer n , cos n θ is a polynomial of degree n in cos θ (it is the Chebyshev polynomial of the first kind). Therefore, the strategy which should be used for solving this problem is to express everything in terms of x = cos θ and then find the minimum of a quartic function obtained.
By using the multiple angle formulae, we easily infer cos 2 θ = 2 x 2 − 1 , cos 3 θ = 4 x 3 − 3 x , cos 4 θ = 8 x 4 − 8 x 2 + 1 . Now, after some manipulation, the original expression becomes f ( x ) = 1 6 x 4 + 3 2 x 3 + 4 8 x 2 + 3 2 x + 7 0 , with derivative f ′ ( x ) = 6 4 x 3 + 9 6 x 2 + 9 6 x + 3 2 = 3 2 ( 2 x + 1 ) ( x 2 + x + 1 ) .
Note that as x 2 + x + 1 = ( x + 2 1 ) 2 + 2 1 > 0 for all real x , the first derivative of f has only one zero, namely − 2 1 . It is well-known that the extremes of f can be obtained only at 3 points - at − 2 1 , and at the boundaries of the intervals at which f is defined, in this case, these are -1 and 1, as − 1 ≤ cos θ ≤ 1 . By hand-checking, the minimum value of the expression is 63.
Using the sum and product formulas, we get that
2 cos 4 θ + 8 cos 3 θ + 3 2 cos 2 θ + 5 6 cos θ + 4 6 = 1 6 cos 4 θ + 3 2 cos 3 θ + 4 8 cos 2 θ + 3 2 cos θ + 1 6 = 1 6 ( cos 2 θ + cos θ + 1 ) 2 = 1 6 ( ( cos θ + 2 1 ) 2 + 4 3 ) 2
This achieves it's minimum when cos θ = 2 − 1 , which has value 1 6 ( 4 3 ) 2 = 9 . Hence, the minimum of the expression is 1 0 0 − 4 6 + 9 = 6 3 .
why cant cos(theta)=-1 i didnt understand
Log in to reply
Would that give the minimum value of the expression?
If you wanted to minimize ( cos θ + 2 1 ) 2 , would that happen at cos θ = − 1 or at cos θ = − 2 1 ?
Log in to reply
got it you are right thank you for helping me
Let cos ( θ ) = x . \begin{align} \cos(2 \theta) & =2 \cos(\theta) - 1 & = 2x^2-1\ \cos(3 \theta) & = 4 \cos^3(\theta) - 3 \cos(\theta) & = 4x^3 -3x\ \cos(4 \theta) & = 2 \cos^2(2 \theta) - 1 = 2(2x^2-1)^2-1 & = 8x^4 - 8x^2+1 \end{align} We want to find the minimum of 2 cos ( 4 θ ) + 8 cos ( 3 θ ) + 3 2 cos ( 2 θ ) + 5 6 cos ( θ ) + 1 0 0 . Equivalently, we can find the minimum of cos ( 4 θ ) + 4 cos ( 3 θ ) + 1 6 cos ( 2 θ ) + 2 8 cos ( θ ) + 5 0 and multiply by 2 . Hence, \begin{align} \cos(4 \theta) + 4 \cos(3 \theta) + 16 \cos(2 \theta) + 28 \cos( \theta) + 50 & = (8x^4 - 8x^2+1) + 4(4x^3-3x) + 16(2x^2-1) + 28x + 50\ & = 8x^4 + 16x^3 + 24x^2 + 16x + 35 \end{align} Since x = cos ( θ ) , we have x ∈ [ − 1 , 1 ] and hence we want to find the minimum of $$f(x) = 8x^4 + 16x^3 + 24x^2 + 16x + 35$$ in the domain x ∈ [ − 1 , 1 ] .
To do this, let us first find f ′ ( x ) . We get that $$f'(x) = 32x^3 + 48x^2 + 48x + 16 = 16(2x^3 + 3x^2 + 3x + 1) = 16(2x+1)(x^2 + x + 1)$$ Setting f ′ ( x ) = 0 , we get that x = − 2 1 , which also lies in the domain [ − 1 , 1 ] . Hence, the global minimum of f ( x ) is $$f(-1/2) = 8 \times \dfrac1{16} - 16 \times \dfrac18 + 24 \times \dfrac14 - 16 \times \dfrac12 + 35 = \dfrac12 - 2 + 6 - 8 + 35 = 31 \dfrac12$$
Hence, the minimum of 2 cos ( 4 θ ) + 8 cos ( 3 θ ) + 3 2 cos ( 2 θ ) + 5 6 cos ( θ ) + 1 0 0 is $$2 \times 31 \dfrac12 = 63$$
2\cos4?+8\cos3?+32\cos2?+56\cos?+100 2\cos 4\theta + 8\cos 3\theta + 32\cos 2\theta + 56 \cos \theta + 100 we substitue all \cos with more than 1 \theta : \cos 4\theta = \cos 2(2\theta) = 2 (\cos 2\theta)^2 -1 = 2 (2\cos^2 \theta -1)^2 -1 = 2 (4\cos^4 \theta - 4\cos^2 \theta +1) -1 = 8\cos^4 \theta - 8\cos^2 \theta + 1
\cos 3\theta = 4\cos^3 \theta - 3 \cos \theta
\cos 2\theta = 2\cos^2 \theta - 1
so we get a new formula :
2\cos 4\theta + 8\cos 3\theta + 32\cos 2\theta + 56 \cos \theta + 100 =16 \cos^4 \theta - 16\cos^2 \theta + 2 + 32 \cos^3 \theta - 24 \cos \theta + 64 \cos^2 \theta - 32 + 56 \cos \theta + 100 =16 \cos^4 \theta + 32 \cos^3 \theta + 48 \cos^2 \theta + 32 \cos \theta + 70
now we are looking for the minimum possible value, so the value of \cos \theta must be negative, and we have choice of -0,5 (\theta = 120^\circ) or -1 (\theta= 180^\circ). because we have \cos^4 \theta and \cos^2 \theta, we will get a positive number from inserting the negative one, so we must minimize both, where we can minimize it by inserting the \theta by 120^\circ so we will get these number : 16 \times 0,0625 + 32 \times (-0,125) + 48 \times 0,25 + 32 \times (-0,5) + 70 = 1 - 4 + 12 - 16 + 70 = \underline{63}
2cos4θ+8cos3θ+32cos2θ+56cosθ+100=2(2(2 cos^(2)θ-1)^(2)-1)+8(4 cos^(3)θ-3 cosθ)+32(2 cos^(2)θ-1)+56 cosθ+100. let cosθ=x ,then equation becomes 16 x^4 +32 x^3 + 48 x^2 +32 x+70 , differentiating and equating to zero to find minima,we get . 64 x^3+96 x^2 +96 x +32=0, x=-1/2 is a valid result (between -1 and 1). Again differentiating and substituting x=-1/2 we get positive value(48), so we confirm that x=-1/2 gives the minimum value of this equation.Thus substituting cosθ=-1/2 we get the value of equation as 67. 16 (-1/2)^4+32 (-1/2)^3 +48 (-1/2)^2 +32 (-1/2)-30+100=67.
[;2cos(4\theta )+8cos(3\theta )+32cos(2\theta )+56cos(\theta )+100 ;] Let [;cos(\theta )=u;] therefore: [;cos(2\theta )=2{ u }^{ 2 }-1;] [;cos(3\theta )={ 4u }^{ 3 }-{ 3u };] ;[cos(4\theta )=2{ ({ 2u }^{ 2 }-1) }^{ 2 }-1={ 8u }^{ 4 }-8{ u }^{ 2 }+1;] Substituting in the above equation we have: [;{ 16u }^{ 4 }+{ 32u }^{ 3 }+48{ u }^{ 2 }+32{ u }+100;] Deriving the expression we find: [;2{ u }^{ 3 }+3{ u }^{ 2 }+3u+1=0;] Now we note that as [;-1\le u\le 1;] as solution of the cubic equation is [;\frac { -1 }{ 2 };] and verification, we see that it is the value that minimizes the expression. Sorry for my bad english.
f ( θ ) = 2 cos 4 θ + 8 cos 3 θ + 3 2 cos 2 θ + 5 6 cos θ + 1 0 0
Simplifying this function to contain only cos θ terms:
f ( θ ) = 1 6 ( cos 4 θ + 2 cos 3 θ + 3 cos 2 θ + 2 cos θ ) + 7 0
f ( θ ) = 1 6 ( A ) + 7 0
Now function will have minimum value if and only if A ≤ 0
Let cos θ = x
So, x 4 + 2 x 3 + 3 x 2 + 2 x ≤ 0
Factorizing, we get x ( x + 1 ) ( x 2 + x + 2 ) ≤ 0
But ( x 2 + x + 2 ) > 0 for all x, so now
x ( x + 1 ) ≤ 0
Case 1:
x ( x + 1 ) = 0 ; which gives either x = 0 or x + 1 = 0
If x = 0 then θ = ( 2 π + n π ) which gives A > 0 and hence f ( θ ) > 7 0
if x = − 1 then θ = ( 2 n + 1 ) π which gives A = 0 and hence f ( θ ) = 7 0
Case 2: x ( x + 1 ) < 0 ; where either x > 0 and x + 1 < 0 and that is not possible. So x < 0 and x + 1 > 0 Simplifying, 0 > x > − 1
0 > cos θ > − 1 that gives
( 2 n + 1 ) 2 π > θ > ( 2 n + 1 ) π
Now we see that among θ = ( 2 π + 3 π ) ; θ = ( 2 π + 4 π ) and θ = ( 2 π + 6 π )
A < 0 only for θ = ( 2 π + 6 π )
So evaluating we get f ( θ ) = 6 3
We want to minimize the function f ( x ) = 2 c o s 4 x + 8 c o s 3 x + 3 2 c o s 2 x + 5 6 c o s x . Now using the sum-to-product identity of cosine we can rewrite f(x) as : f ( x ) = 4 c o s ( 2 7 x ) c o s ( 2 1 x ) + 6 4 c o s ( 2 3 x ) c o s ( 2 1 x ) + 2 4 c o s x + 6 c o s 3 x . Now, since 64 is greater than the sum of the other "coefficients" (which is 34) and − 1 ≤ c o s x ≤ 1 , f(x) is minimized when 6 4 c o s ( 2 3 x ) c o s ( 2 1 x ) is minimized. But it is easy to see that 6 4 c o s ( 2 3 x ) c o s ( 2 1 x ) is minimized when x = 3 2 π . Now substituting x = 3 2 π in f(x) we obtain f(x)=-37. Now to obtain the desired result we must add 100 to -37 which makes 63.
The derivative is − 8 ( s i n θ + 3 s i n 2 θ + 8 s i n 3 θ + 7 s i n 4 θ ) .
For θ = 3 2 π it is null: s i n θ + 3 s i n 2 θ + 8 s i n 3 θ + 7 s i n 4 θ = 2 1 ( − 1 + 8 + 0 − 7 ) = 0 .
I can't demonstrate that this local min is global, I guessed it from the plot :(
c o s 4 θ = 8 c o s 4 θ − 8 c o s 2 θ + 1 , c o s 3 θ = 4 c o s 3 θ − 3 c o s θ , c o s 2 θ = 2 c o s 2 θ − 1 . Substitute for these into the equation, and let x = c o s θ . The statement now translates to finding minimum of, say y = 1 6 x 4 + 3 2 x 3 + 4 8 x 2 + 3 2 x + 7 0 . Taking d x d y = 0 , we get 2 x 3 + 3 x 2 + 3 x + 1 = 0 .
ie, x 3 + ( 1 + x ) 3 = 0 for − 1 ≤ x ≤ 1 ,
− x 3 = ( 1 + x ) 3 for − 1 ≤ x ≤ 1 .
Only x = 2 − 1 satisfies this equality by taking cube root on both sides. Also, d x 2 d 2 y is > 0 at x = 2 − 1 . Therefore we have a minimum at x = 2 − 1 . Substituting this value, we get minimum value of y = 6 3 .
Problem Loading...
Note Loading...
Set Loading...
For positive integers k , ( cos θ + i sin θ ) k = e k i θ = cos k θ + i sin k θ , so equating real parts and using sin 2 θ = 1 − cos 2 θ gives us an expression for cos k θ in terms of cos θ . For convenience, let x = cos θ ∈ [ − 1 , 1 ] . Then cos 4 θ = 8 x 4 − 8 x 2 + 1 , cos 3 θ = 4 x 3 − 3 x , and cos 2 θ = 2 x 2 − 1 [Note: Or you can obtain this by the sum and difference formulas - Calvin]
So, 2 cos 4 θ + 8 cos 3 θ + 3 2 cos 2 θ + 5 6 cos θ + 1 0 0 can be rewritten as 2 ( 8 x 4 − 8 x 2 + 1 ) + 8 ( 4 x 3 − 3 x ) + 3 2 ( 2 x 2 − 1 ) + 5 6 x + 1 0 0 which is equal to 1 6 x 4 + 3 2 x 3 + 4 8 x 2 + 3 2 x + 7 0 = 1 6 ( x 2 + x + 1 ) 2 + 5 4 where we use the factorization x 4 + 2 x 3 + 3 x 2 + 2 x + 1 = ( x 2 + x + 1 ) 2 .
But x 2 + x + 1 = ( x + 2 1 ) 2 + 4 3 is clearly minimized over the interval [ − 1 , 1 ] at x = − 2 1 , so the desired minimum is 1 6 ( 4 3 ) 2 + 5 4 = 6 3 .